Transparent low-voltage-driven soft actuators with silver nanowires Joule heaters - Liu, Jian (2022)
Transparent soft actuators have been receiving enormous attention due to their potential for application in camouflage robotics, accurate monitoring/controlling of soft robots, etc. Herein, we report an electrically powered soft actuator relying on reversible nematic-to-isotropic transitions of liquid crystalline elastomers (LCEs) induced by Joule heating with silver nanowires (AgNWs). Taking advantage of the high conductivity and transparency of the AgNWs electro-heater, the assembled soft actuator can attain high transmittance (60-70%) in the visible region. It exhibits a large bending deformation upon the application of a low voltage of 6 V within 20 s, and returns to its original state when withdrawing the voltage. In addition, the degree of bending can be controlled by the voltage applied and application time of the electric field. The LCE-based transparent soft actuators with low voltage switching are particularly promising for application in smart soft robots with optical components.